Antenatal and Postnatal Diagnosis of Coxsackie B4 Infection: Case Series - Jennifer C. Hunt; Carol Schneider; Savas Menticoglou; Jayantha Herath; Marc R. Del Bigio (Thieme Medical Publishers, Inc., 2012)
Enteroviruses are a common cause of neonatal infection. In particular, Coxsackie B viruses are often associated with severe, fatal disease. The antenatal diagnosis of Coxsackie B viral infections is uncommon. We present a unique case of Coxsackie B4 virus ventriculitis and myocarditis causing fetal hydrops at 22 weeks gestation. Transmission was inferred by viral isolation from the amniotic fluid and by placental pathology. We also describe two additional cases of fatal neonatal Coxsackie B4 infection complicated by myocarditis and encephalitis with cerebral necrosis in a 4-day-old female and by myocarditis, spinal leptomeningitis, and hepatitis in a 4-day-old male. Transplacental acquisition of infection carries a poor prognosis. We propose that Coxsackie B virus should be considered in the investigation of nonimmune hydrops, particularly in the presence of cardiac dysfunction.